Exercise performance at different phases of the menstrual cycle: measurements, differences, and mechanisms - a narrative review - Wen, Yiqing; Gao, Binghong; Wang, Renwei; Zhao, Can (Frontiers in Endocrinology, 2025)
With the increasing participation of women in sports, research on women’s sports has gradually increased but remains less than that on men’s sports as a whole. The menstrual cycle is a unique physiological feature of women. Hormone fluctuations during this period can have a potential effect on exercise performance through various mechanisms, including substrate metabolism, cardiopulmonary function, body temperature regulation, and psychological factors. This narrative review analyzed the changes in aerobic performance, anaerobic performance, and strength during the menstrual cycle by analyzing domestic and international research on exercise performance at different phases of menstrual cycle and preliminarily discussed the influence of menstrual cycle-related factors on exercise performances. Results show that although a considerable proportion of female athletes believe that their exercise performance is affected by their menstrual cycle (poor exercise performance during the early follicular and midluteal phases), various exercise performance during different phases of the menstrual cycle are inconsistent. Such variability may be related to the inconsistency of current research methods, such as the method for identifying menstrual cycle phases. Current research focuses on aerobic, anaerobic, and strength indices, and only a few studies on speed, sensitivity, and flexibility exist. Studies that support the differences in transport performance during different menstrual cycle phases have the overall consensus that aerobic performance in the follicular phase is higher than that in the luteal phase and the effect of hormonal fluctuations on aerobic performance during the menstrual cycle can be reduced by ingesting glucose. Maximum strength is poorest during the luteal phase. However, strength training can be planned on the basis of the hormone fluctuation characteristics of the menstrual cycle. Most studies have shown that anaerobic performance is unaffected by the menstrual cycle. Further research is needed to quantify exercise performance during different phases of the menstrual cycle and determine the relevant factors affecting exercise performance to understand women’s exercise performance fully. It provides help to athletes in regulating their physiological cycle before games and ensuring their maximum performance during competition.